2010
DOI: 10.2478/v10051-010-0007-0
|View full text |Cite
|
Sign up to set email alerts
|

Educational Institution's Image: A Case Study

Abstract: Educational Institution's Image: A Case StudyThis article presents our findings about the factors influencing educational institution's image. Based on the literature review we composed a web questionnaire which was send to all current students at University of Maribor's Faculty of Organizational Studies. Based on our research results we found out that eight factors influence educational institution's image which have various amounts of influence on the educational institutions image. The factor with the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 19 publications
(28 reference statements)
1
22
0
2
Order By: Relevance
“…A physically present research assistant presented a standard introductory text before completion and offered assistance if necessary. Results indicate that from the prospect of teaching quality, higher educational institutions will improve their repute if promoting information about the expertise of their teachers, describing their curriculum and benchmarks, providing descriptions or demonstrations of the various teaching methods and sources used (in accordance with previous findings, see Kandiko & Mawer, 2013;Marič, et. al., 2010).…”
Section: Methodssupporting
confidence: 77%
“…A physically present research assistant presented a standard introductory text before completion and offered assistance if necessary. Results indicate that from the prospect of teaching quality, higher educational institutions will improve their repute if promoting information about the expertise of their teachers, describing their curriculum and benchmarks, providing descriptions or demonstrations of the various teaching methods and sources used (in accordance with previous findings, see Kandiko & Mawer, 2013;Marič, et. al., 2010).…”
Section: Methodssupporting
confidence: 77%
“…In literature, there have been various studies regarding the measurement of perceived university image [35,52] and variables that affect perceived university image. William and Moffit [57] stated in their study that perceived image has a large and determining effect on the members of institution.…”
Section: Perceived University Imagementioning
confidence: 99%
“…Traverso (2002) identified the equipment and resources of a university, the quality of the teaching staff and the facilities, as elements through which students build their image of a university. Helgesen and Nesset (2007) came to a similar conclusion, detecting a positive significant relation between facilities and university image, and Maric et al (2010) identified the quality of the teaching staff as the most relevant variable in image formation. In this research, the "teaching resources" dimension was conceived to be society's perception of the availability and quality of a university's resources for providing services.…”
Section: Conceptualization Of the University Image: A Higher-order Fomentioning
confidence: 66%
“…Perception of graduate training. There are several works whose results have suggested that the orientation and training that a university provides its students (Beerli et al 2002;Traverso 2002), opportunities for its graduates to make a transition into employment (Duarte et al 2010;Matherly 2012), and the quality of study plans (Traverso 2002) and learning contents (Maric et al 2010) exert a relevant positive influence on university image. Based on these works, we considered the dimension "graduate training" and defined it as society's perception of the skills a university develops in its students so they can take up a job after concluding their studies.…”
Section: Conceptualization Of the University Image: A Higher-order Fomentioning
confidence: 99%